Afatinib in EGFR TKI-Naïve Patients with Locally Advanced or Metastatic EGFR Mutation-Positive Non-Small Cell Lung Cancer: A Pooled Analysis of Three Phase IIIb Studies - Passaro, Antonio; de Marinis, Filippo; Tu, Hai-Yan; Laktionov, Konstantin K.; Feng, Jifeng; Poltoratskiy, Artem; Zhao, Jun; Tan, Eng Huat; Gottfried, Maya; Lee, Victor; Kowalski, Dariusz; Yang, Cheng Ta; et al. (Frontiers in Oncology, 2021)
Background: Afatinib is approved for first-line treatment of patients with epidermal growth factor receptor mutation-positive (EGFRm+) non-small-cell lung cancer (NSCLC). Here, we report findings from a combined analysis of three phase IIIb studies of afatinib in EGFR tyrosine kinase inhibitor (TKI)-naïve patients. Methods: EGFR-TKI-naïve patients with EGFRm+ NSCLC received afatinib 40 mg/day. Dose reductions were permitted for adverse events (AEs). Efficacy endpoints included progression-free survival (PFS), time to symptomatic progression (TTSP), and tumor response. Subgroup analyses were performed by Eastern Cooperative Oncology Group performance status (ECOG PS), presence of brain metastasis, age and common/uncommon EGFR mutations (plus other factors). Results: 1108 patients were treated. Median age was 61 years (range, 25–89); 19.2% had baseline brain metastases, 4.4% had ECOG PS ≥2, and 17.9% had tumors harboring uncommon mutations. Treatment-related AEs (TRAEs) were reported in 97.2%, most commonly diarrhea and rash. 41.6% had AEs leading to dose reduction. Median PFS was 13.0 months (95% confidence interval [CI]: 12.0–13.8); median TTSP was 14.8 months (95% CI: 13.9–16.1). Objective response rate (ORR) was 55.0%. Age, presence of baseline brain metastases, major (G719X, L861Q, S768I) or compound uncommon mutations had little/no effect on PFS, TTSP, or ORR, while outcomes were poorer in patients with ECOG PS 2 or exon 20 insertion/T790M mutations. Conclusions: Afatinib was tolerable with no new safety signals Afatinib demonstrated encouraging efficacy in a broad patient population, including those with brain metastases or uncommon EGFR mutations.